Concept of Accountability Settlement Past Gross Human Rights Violations in Indonesia - Husni Thamrin (Ipso Jure, 2024)
The Indonesian government is now seeking to resolve the country's past egregious human rights crimes. Although the current policies are encompassed within the regulatory framework concerning this issue: Legal disputes and activities that do not involve going to court. In the eyes of justice, these two approaches are not an option but a combination that can be used together. The problem is that the government's only choice leads to one solution: settlement outside the court. Methodology: Researchers compared settlement practices in several countries to conclude how Indonesia should solve past gross human rights violations. Finding: The ideal concept of state accountability for Past Serious Human Rights Violations in Indonesia consists of three ways, firstly by continuing its legal process to be completed through justice mechanisms such case 1998 Kidnapping Activist, Mysterious Shooting (Penembakan Misterius-Petrus), May 1998 Riots, Trisakti Student Shooting and Semanggi I-II case of 1998-1999 and Talangsari Case. The settlement was conducted by the Truth Commission for Reconciliation, addressing various cases of human rights violations. These include the 1965 case, human rights violations in Aceh from 1976 to 1998, such as the incidents at Rumoh Geudong, Sattis Aceh Post in 1989, and the Simpang KKA case in 1999. Additionally, it addressed human rights violations in Tanjung Priok, the murder of Dukun Santet from 1998 to 1999, and human rights violations in Papua from 1965 to 1998. Finally, making arrangements for legal processes regarding cases that took place after the implementation of the Human Rights Court Law, such as the Wasior Papua case from 2001-2002, the Wamena Papua case from 2003, and the Jambo Keupok Aceh case from 2003.